Genetic diversity and population structure of a core collection of Mediterranean durum wheat accessions using DArTseq markers - Laribi, Marwa; Ben M’Barek, Sarrah; Velasco-Cuervo, Sandra M.; Hwang, Sheau-Fang; Yahyaoui, Amor H.; Strelkov, Stephen E. (Springer, 2025)
Background Durum wheat was domesticated in the Fertile Crescent and later spread to the Mediterranean, where human and natural selection led to the establishment of local landraces. Since the 1970s, elite durum wheat varieties largely replaced these landraces. However, landraces continue to play an important role in broadening genetic diversity and contributing valuable traits to modern wheat, particularly in the Mediterranean region, which accounts for 45% of global durum wheat production. This study examined the genetic diversity and population structure of 258 durum wheat genotypes, comprising 125 landraces, 54 breeding lines, 43 cultivars, 34 accessions of uncertain improvement status, and two near-isogenic lines. These genotypes originate primarily from various countries in the Mediterranean basin, including Algeria (39 genotypes), Egypt (3), France (45), Israel (2), Italy (54), Jordan (2), Morocco (2), Portugal (51), Spain (50), Tunisia (6), and Turkey (4).